Tunable 1st Order IIR Phase Shifter Design and Implementation - Chivapreecha, Sorawat; Jongsataporn, Thitaphan (My University, 2024)
This paper presents a new phase shifter which is a first-order infinite impulse response (IIR) filter that can shift phase both in phase-lead (0° to+180°) and phase-lag (-180° to 0°) fashion. Moreover, continuous phase tuning is also proposed in our phase shifter. The z-transform pair of phase-shifted cosine signal is utilized as the origin, then factorization of such term can give transfer function of first-order IIR phase shifter. The filter structure realization of the tunable phase shifter will be shown and applied with a digital cosine oscillator. Both simulation and hardware experiments can show phase-shifted signals in real-time controlled by phase-tuning parameters compared with a cosine reference signal as a demonstration. The allpass phase shifter will be used as a benchmark, and trade-off analysis using the proposed phase shifter will also be discussed.
Keywords: allpass filter; arbitrary phase shift; Digital phase shifter; IIR filter; tunable phase